A survey of mineral status of soils, feeds and cattle in the Selale Ethiopian highlands. I. Macro elements - Khalili, M.; Lindgren, E.; Varvikko, T. (Springer, 1993)
The macro mineral status of cattle in the Selale highlands of Ethiopia was evaluated during the rainy and dry seasons of 1989 and 1990 in terms of mineral concentrations in soils, feeds, blood plasma and faeces on 25 farms. Bone samples from animals of local breeds from a slaughter house were collected during the rainy season and dry seasons of 1990. Soils were analysed for PH, organic matter, Ca, P, Mg, Na and K. The results indicated wide variation in the concentrations of minerals on different farms. Available feeds in the area consist of pasture, hay, barley straw, oats and teff, and the grains of barley and oats. Pasture grass and other feeds were found to be deficient in Na, P and Mg in relation to dietary requirements. Analyses of blood plasma from crossbred and local cattle showed that a number of samples contained P below the critical level of 1.45 mmol/litre. Effects of year and season were significant for Ca, P, Mg and K. The effect of age was significant for Faecal analyses revealed that about 80 percent of animals were deficient in Na. Wide variations in the mineral content of soils and lack of significant correlations among soil, pasture and blood plasma indicated that soil and pasture analyses are not reliable in assessing macro mineral status of grazing cattle in this environment. Analyses of bone and blood for Ca and P, blood for Mg and faeces for Na appear to provide better indices.